2 - Reality Checks: The state of civil society organizations in Ethiopia - Yntiso Gebre (African Sociological Review, 2016)
The general literature on the state of civil society organisations (CSOs) in Ethiopia gives the impression that CSOs have been rendered dysfunctional by the restrictive law passed in 2009. While considerable attention has been given to the devastating effects of the CSO law on human rights groups, the successful stories of the overwhelming majority of organisations engaged in development and service delivery have been overlooked. The law does limit the space for CSOs working on human rights and governance and it is legitimate and ethical to challenge the restrictive provisions on constitutional, legal, moral and/or practical grounds. However, it is equally important to recognize the continued operations of numerous CSOs, their contributions to national development priorities, their innovativeness in dealing with sensitive rights issues, the role of donors in supporting CSOs and the responses of the government to the request for a more enabling environment. This paper contains contextualized arguments based on empirical data as reality check on the current state of CSOs in Ethiopia.